2003
DOI: 10.1161/01.atv.0000074145.58172.bd
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Genotype 325–Specific proCPU/TAFI ELISA

Abstract: Objective-A Thr/Ile polymorphism at position 325 in the coding region of proCPU has been reported. Immunological assays, fully characterized (including genotype dependency), are required for the quantitation of proCPU levels. Methods and Results-We have generated a panel of monoclonal antibodies against human, plasma-derived proCPU. Two combinations exhibiting distinct reactivities were selected for measurement of proCPU in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 32 publications
1
100
1
6
Order By: Relevance
“…[11][12][13][14][15] Alternatively, clot lysis experiments 31 or the use of fluorescently labeled plasminogen 32 may also be used to quantitate TAFI levels or TAFIa activity, respectively. Apart from a previous study 16 demonstrating that the reactivity of a majority of available assays is partially dependent on the Thr 325 polymorphism, it should be realized that interpretation of TAFI antigen levels as determined with noncharacterized immunologic assays is also quite ambiguous because TAFI can occur in different forms (TAFI, TAFIa, TAFIai, fragmentation products of TAFIai, released AP). Therefore, there is currently a strong need for well-characterized immunoassays for the evaluation of the levels of different TAFI forms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[11][12][13][14][15] Alternatively, clot lysis experiments 31 or the use of fluorescently labeled plasminogen 32 may also be used to quantitate TAFI levels or TAFIa activity, respectively. Apart from a previous study 16 demonstrating that the reactivity of a majority of available assays is partially dependent on the Thr 325 polymorphism, it should be realized that interpretation of TAFI antigen levels as determined with noncharacterized immunologic assays is also quite ambiguous because TAFI can occur in different forms (TAFI, TAFIa, TAFIai, fragmentation products of TAFIai, released AP). Therefore, there is currently a strong need for well-characterized immunoassays for the evaluation of the levels of different TAFI forms.…”
Section: Discussionmentioning
confidence: 98%
“…15 A possible explanation for these contradictory results was that the different studies used different methods for TAFI determination. 16 Silveira et al used quantitative activation of the zymogen followed by determination of the total enzymatic activity with a chromogenic assay. Van of TAFI antigen levels, as a putative risk marker for cardiovascular events, has been mainly focused on "total" antigen levels (either by ELISA or by activity assays after full activation of TAFI), reporting levels of 4 to 15 g/mL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several different antigen assays as well as distinct activity assays have been used in epidemiological studies. With the discovery that some enzyme linked immunosorbent assays of TAFI antigen are dependent on the 1040C/T polymorphism, revealing a lack of reactivity with the 1040T variant, 21 even more caution is required in the interpretation of results.…”
Section: Introductionmentioning
confidence: 99%
“…10 -12 Furthermore, a combined segregation-linkage analysis suggested the existence of 2 quantitative trait loci that would explain 78% of the variance in plasma TAFI Ag. 13 However, it was demonstrated that some ELISAs used for TAFI Ag determination had different assay sensitivity between isoforms, 14,15 leading to overestimations of the effects associated with TAFI gene polymorphisms. Results from recent studies using genotype-independent assays have confirmed a genetic effect although of lesser magnitude.…”
mentioning
confidence: 99%